(untitled) (Journal of Hama University, 2021)
Introduction:The objective of border molding procedure is to get peripheral seal to achieve a retentive denture. Border molding record is influenced by the material and technique. Aim: To compare the single‑step border molding technique using putty viscosity of Poly vinyl siloxan addition silicone with sectional border molding technique using low fusing impression compound by evaluating the retention of heat cure trial denture bases. Materials and Methods: Twelve completely upper edentulous patients were selected to evaluate the retention of acrylic denture bases provided by two different final impression techniques(sectional border molding using low fusion impression compound, single step border molding using putty viscosity of PVS )and the two techniques followed by a final wash impression using light bodied of PVS material, then a digital force meter was used to measure retention strength provided by each technique. Results: the statistical analysis showed no significant difference in bases retention between the two border molding techniques. Conclusions: within the limits of this study ,it can be concluded that single step border molding using putty silicon provided similar clinical retention on denture bases compared to sectional border molding using low fusing impression compound.